Increased Basement Membrane Components in Adipose Tissue During Obesity: Links With TGFβ and Metabolic Phenotypes - Reggio, Sophie; Rouault, Christine; Poitou, Christine; Bichet, Jean-Christophe; Prifti, Edi; Bouillot, Jean-Luc; Rizkalla, Salwa; Lacasa, Danièle; Tordjman, Joan; Clément, Karine (The journal of clinical endocrinology and metabolism, 2016)
Context:Collagen accumulation around adipocytes and vessels (ie, pericellular fibrosis) is a hallmark of obese adipose tissue associated with altered metabolism.Objective:Our objective was to evaluate components of basement membrane (BM) in adipose tissue, including collagen IV, a major BM component, and its relationships with metabolic parameters and TGFβ isoforms.Design and Setting:We used immuno-techniques and gene expression approaches to detect BM components in subcutaneous and visceral adipose tissue samples. Adipocytes and endothelial cells were isolated from lean and obese adipose tissue. We also focused on the expression of COL4A1 correlated to metabolic variables in moderate obesity and, in severe obesity before and after bariatric surgery. Using in vitro analysis, we explored the impact of TGFβ isoforms on the expression of inflammatory and extracellular matrix genes in adipocytes and endothelial cells.Results:BM components were detected around adipocytes and endothelial cells, and were increased in obese adipocytes. COL4A1 expression was positively correlated with insulin-resistance indices in obese subjects and showed less reduction in severely obese subjects with poorer insulin-resistance outcomes 6 months after gastric bypass. COL4A1 expression also correlated with TGFβ1 and TGFβ3 gene expressions in subcutaneous adipose tissue. Stimulating isolated adipocytes and endothelial cells in vitro with these TGFβ isoforms showed an inflammatory and pro-fibrotic phenotype. However, TGFβ1 and TGFβ3 exposure only provoked COL4A1 overexpression in endothelial cells and not in adipocytes.Conclusion:The disorganization of several BM components, including collagen IV, could contribute to pathological alterations of obese adipose tissue and cells.